Loneliness and mental burden among German medical students during the fading COVID-19 pandemic: a mixed-methods approach - Marvik Leich; Jennifer Guse; Corinna Bergelt; Corinna Bergelt (Frontiers in Psychology)
IntroductionMedical students experience significantly more mental burdens compared to the general public. This circumstance was further exacerbated by the pandemic, particularly with regard to loneliness. While previous studies have identified risk factors for loneliness among students of different subjects, recent data focusing on medical students during the late stages of the pandemic remain insufficient. This study aims to address this gap.MethodsWe performed a cross-sectional study at a German Medical School, consisting of two online surveys conducted in winter 2021/22 and summer 2022. The study sample, composed of 283 undergraduate students in winter 2021/22 (231 in summer 2022), answered five well-established scales for measuring loneliness (R-UCLA3), distress (DT-NCCN), anxiety (GAD-2), depression (PHQ-2), and perceived stress (PPS-4). Additionally, we evaluated burdensome aspects of students' current situation through qualitative analysis. Longitudinal analyses were conducted for 80 medical students who participated in both surveys.ResultsAround 20% of all students responded to each survey. In winter 2021/22, 55.1% of students reported loneliness above the cut-off (M = 5.77 [2.02]; decreasing to 45.0% by summer 2022 (M = 5.22 [1.90]). Lonely students reported significantly higher levels of depression, anxiety, and self-perceived stress in both survey periods. Overall distress increased substantially throughout our study (Cohen's d = −0.54). Binary regression models indicated a shift in loneliness risk factors: in winter 2021/22, being single, higher self-perceived stress levels, and decreased study motivation were associated with increased loneliness. Lower peer connectedness emerged as the sole significant factor associated with loneliness in summer 2022. While the pandemic-related burden on students' study motivation lessened, issues related to exam preparation and lack of study organization through the faculty increased, varying significantly depending on students' study year.ConclusionOur data suggest that loneliness among German medical students decreased in the late stages of the COVID-19 pandemic. However, other mental burdens persisted at high levels compared to other data in the general public and medical students. Students' responses underscore the need for improved academic support by eased study program structure, improved counseling, and tailored services for students of different study years.